On the Issue of the Effectiveness of Legal Regulation Based on Psychological Aspects - Belyaev, Valery P. (2020)
This article is devoted to the analysis of problems regarding the main approaches to understanding the effectiveness of legal regulation and the search for its criteria. It is known that this issue serves as the basis for ongoing social development, ensuring optimal law-making and law enforcement activities of state bodies, achieving the goals of the procedural and legal regulation, consisting in ensuring, within certain stages of the legal and reasonable consideration and resolution of legal cases, the adoption of appropriate procedural decisions in the interests of subjects of law. The effectiveness of legal regulation is determined by a kind of evaluation category, the essence of which is to determine the level of functionality and effectiveness of this process in its dynamics. As criteria for the effectiveness of procedural and legal regulation are called effectiveness, achievement of the goal, procedural savings and others.